The extended uncertainty principle effects on the phase transitions of Reissner-Nordström and Schwarzschild black holes - Özgür Ökcü; Ekrem Aydiner (Nuclear Physics B, 2022)
In this paper, we investigate the phase transitions of Reissner-Nordström (RN) and Schwarzschild black holes for the extended uncertainty principle (EUP) framework. Considering temperature T, charge Q and electric potential Φ as the state parameters, we show the van der Waals (vdW) like phase transition of RN black hole in Q−Φ diagrams and find the critical points depending on EUP parameter α. Furthermore, we find Hawking-Page like phase transition for Schwarzschild black hole. The results imply that the black holes in asymptotically flat space have the similar phase structure with the black holes in anti-de Sitter (AdS) space.